Assessing effectiveness in acne clinical trials: steps towards a core outcome measure set. (1st October 2019) - Thiboutot, D.M.; Layton, A.M.; Chren, M.‐M.; Eady, E.A.; Tan, J.
Summary: Background: Acne ranks second to dermatitis in terms of global burden of skin disease. As such, it is essential that data on treatment efficacy are generated in a way that maximizes the opportunity for comparison among treatments. Interest in developing core outcome sets for use in clinical trials to standardize data collection in skin disease is surging. Objectives: The goal of this review is to provide an update on the efforts underway, challenges encountered and future directions in the development of an acne core outcome measure set for use in clinical trials. Methods: The activities of the Acne Core Outcomes Research Network (ACORN) are presented in the context of currently acceptable methodologies for core outcome set development. Conclusions: Emphasis is placed on following a rigorous methodology, involving patients and recognizing a role for emerging technologies.